2022
DOI: 10.3390/su14159483
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Thermo-Electrochemical (TEC) Cell Performances for Harvesting Low-Grade Heat Energy: A Review

Abstract: Thermo-electrochemical cells (also known as thermocells, TECs) represent a promising technology for harvesting and exploiting low-grade waste heat (<100–150 °C) ubiquitous in the modern environment. Based on temperature-dependent redox reactions and ion diffusion, emerging liquid-state thermocells convert waste heat energy into electrical energy, generating power at low costs, with minimal material consumption and negligible carbon footprint. Recent developments in thermocell performances are reviewed in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 105 publications
0
10
0
Order By: Relevance
“…However, some recent studies have reported record conversion efficiencies of 11% by establishing high concentration ratios at the cold and hot ends [ 74 ]. The Seebeck coefficient, conductivity, power density, and number of charge/discharge cycles of some thermogalvanic hydrogels is shown in Table 1 [ 21 , 23 , 45 , 56 , 75 ]. Despite these low efficiencies, since the primary use of thermogalvanic hydrogels is to harvest wasted energy, the efficiency requirements for commercial viability are relatively low.…”
Section: Improving the Efficiency Of Single Thermocellmentioning
confidence: 99%
See 2 more Smart Citations
“…However, some recent studies have reported record conversion efficiencies of 11% by establishing high concentration ratios at the cold and hot ends [ 74 ]. The Seebeck coefficient, conductivity, power density, and number of charge/discharge cycles of some thermogalvanic hydrogels is shown in Table 1 [ 21 , 23 , 45 , 56 , 75 ]. Despite these low efficiencies, since the primary use of thermogalvanic hydrogels is to harvest wasted energy, the efficiency requirements for commercial viability are relatively low.…”
Section: Improving the Efficiency Of Single Thermocellmentioning
confidence: 99%
“…Among them, applications of inorganic semiconductive thermoelectric generators are expensive, have mechanical brittleness, and are challenging to synthesize. Their thermoelectric efficiency is limited not only by the small Seebeck coefficient (thermodynamic quantity, determined by the change in the electron chemical potential caused by temperature changes) of about 100–200 μV K −1 but also by the electrical and thermal conductivity [ 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…48 To date, numerous review articles have assessed the research progress of ionic liquids-based thermo-electrochemical cells from various standpoints. 49,316,318,321 For instance, Wang et al 318 summarized some common ionic thermoelectric materials and their related thermoelectric conversion mechanism. Li et al 316 fully discussed recent research progress and thermoelectric performance of p-type and n-type thermoelectric cells.…”
Section: T B T T ( ) Exp( /(mentioning
confidence: 99%
“…For steady operation of the latter, the reactants must either be recirculated or the electrodes sequentially heated and cooled [10]. In addition to these different concepts, TGCs also vary in redox couples and electrolytes, which is well summarized in [11]. Due to its increasing availability and without any climate impact, the use of green hydrogen as a reactant in TGC shows great potential, which has already been proven in other thermoelectric energy converters [12][13][14].…”
Section: Introductionmentioning
confidence: 99%